Effects of carburization on expected fatigue life of alloys steel shafts - Loganathan T.M.; Purbolaksono J.; Inayat-Hussain J.I.; Wahab N. (2023)
The motivation of this work is to improve fatigue life of the alloys steel power transmission shafts of the palm oil screw press machines in a Malaysia palm oil company. In order to improve daily productions of the palm oil, a high extraction efficiency of the machine with bigger crushing forces are required. Consequently, the failures due to torsional fatigue would become susceptible to the shafts. The shaft materials of SAAB 709 which has nearest equivalent properties to AISI4140 were then taken for sequential treatments and examinations. Carburizing processes with different combinations of soaking temperatures of 850 C and 900 C and soaking times of 2. h and 4. h were carried out. Standard mechanical tests were then conducted for determining the hardness and the ultimate tensile strength of the specimens. Different soaking temperature and time would result in different carburizing depths that in turn influence the fatigue endurance limit under bending torsional loadings. 2011 Elsevier Ltd.